Diagnosis Dan Tatalaksana Luka Bakar Pada Mata - Diptha Renggani Putri; Rani Himayani (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Introduction: Chemical eye burns, thermal burns, and radiation represent cases that often occur in cases in the emergency department in the eye area. Exposure to body fluids and cyanoacrylates (super glue) also often occur. These conditions if not followed up quickly will result in a poor prognosis. Objective: To determine the initial diagnosis and treatment of eye burns. Method: This article was created using the literature review method, involving 22 libraries both national and international books and journals. Results: Chemical burns represent the most frequent and potentially blind eye injury, this is an eye emergency that requires immediate treatment and starting treatment. The majority of victims are young and exposure can occur at home, work and can also be related to crime. Discussion: Alkaline injuries occur more frequently than acid injuries. Chemical injury to the eye results in extensive damage to the surface epithelium of the eye, cornea, anterior segment, and stem cells resulting in unilateral or bilateral permanent vision damage. Rapid and appropriate management is perhaps the most important factor in determining the final outcome. Conclusion: This article reviews emergency management and new techniques for improving the prognosis of patients with eye burn injuries. Keywords: Acid, alkali, chemical burns, thermal burns, eyes, radiation.